Stress Investigation of Aluminium Alloy and Composite Material for Unmanned Aerial Vehicle Application via Simulation Analysis - Shahrul Hairi, Shahrul Malek Faizsal; Ariffin, Ahmad Hamdan; Mohd Saleh, Siti Juita Mastura; Omar, Zamri (Progress in Aerospace and Aviation Technology, 2022)
Composite material offers excellent properties such as lightweight, high strength to weight ratios, and excellent corrosion resistance. Universiti Tun Hussein Onn Malaysia successfully developed a Cargo Drone (C-Drone) using aluminium alloy as its structure. The future enhancement is looking at the potential of composite material for C-Drone application. Therefore, this research aims to study the stress properties of aluminium alloy and glass fibre composite for C-Drone application via simulation analysis. The scope of this study focuses on the landing gear part of the C-Drone. The drawing of C-Drone was analysed through SolidWorks software to obtain the result of the material reacting to stress, strain, and displacement. The result shows that glass fibre with brittle properties can withstand a high amount of stress, acceptable strain rate, acceptable deformation and reduced weight up to 10% compared to aluminium alloy. This research proves that composite material such as glass fibre reinforced plastic can become an alternative to the current aluminium alloy 6061-T6.